Enhancement of Heat Transfer in a Square Duct with Double V-Ribbed Tape Vortex Generators - ชมภูคำ ธีรพัฒน์ (KKU Science Journal, 2014)
The paper presents an experimental study on turbulent flow and heat transfer characteristics in a square duct fitted diagonally with double V-ribbed tapes. The tested duct has uniform heat-fluxed walls and the flow rate of air used as the test fluid is presented in terms of Reynolds number from 4,000 to 25,000. The insertion of the ribbed tape is performed with three blocked ratios of rib-to-duct height (b/H) = 0.10, 0.15 and 0.20, three attack angles ( ) = 20o, 30o and 45o, pitch ratios of rib pitch to duct height (PR = P/H) = 1 and pointing downstream of the flow with respect to the main flow direction. Influences attack angles and blocked ratios on thermal and flow friction characteristics of the inserted duct are investigated. The experimental result of heat transfer in the form of Nusselt number and pressure drop in term of friction factor are compared between the duct mounted with double V-ribbed tapes and the smooth duct. The experimental result shows that the rise of the attack angle and the blocked ratio results in the increase in Nusselt number and friction factor values. The maximum thermal performance is found to be 1.92 for using the ribbed tape at = 20o and BR = 0.20 at the lowest value of Reynolds number.